Polarized we trade?: Intraparty polarization and US trade policy - Friedrichs, Gordon (International politics, 2022)
Research indicates that polarization has led to an increasing dispersion between moderate and more extreme voters within both parties. Intraparty polarization supposedly affects the nature of interparty competition as it creates political space for new political realignments and the rise of anti-establishment candidates. This article examines the extent and impact of intraparty polarization in Congress on US trade policy. Specifically, the article examines whether (and which) trade policy preferences are distributed within and between both parties, as well as how intraparty polarization has influenced the outcome of US trade negotiations. It is theorized that intraparty polarization causes crosscutting legislative coalitions around specific trade policies and political realignments around ideological factions, with consequences for the outcome of trade negotiations. By relying on a unique dataset of congressional letters and co-sponsorship legislation, the article first derives trade policy preferences from members of Congress and computes their ideological means. Two contemporary cases of US trade policy are examined: The Transpacific Partnership Agreement and the US-Mexico-Canada Agreement. Via a structuredfocused comparison of both cases, the paper finally assesses under which combinations of preference-based and ideology-based intraparty polarization Congress manages to ratify trade agreements. Findings suggest that both parties are intrinsically polarized between free trade and fair trade preferences yet show variance in their degree of ideology-based intraparty polarization. These findings contribute to existing work on bipartisanship as well as factions in the foreign policy realm, as it shows under which circumstances legislators can build crosscutting coalitions around foreign policies.
Online veröffentlicht: 2. August 2021
Gesehen am 17.04.2023